Investigating the Use of Active Learning Methodologies in Programming Education: Findings From a Brazilian National Survey - Calderon, Ivanilse; Oran, Ana Carolina; Silva, Williamson; Feitosa, Eduardo (IEEE-RITA, 2025)
Teaching programming requires instructors to help students develop complex problem-solving and logical reasoning skills. Active Learning Methodologies (ALMs) have the potential to enhance this process, but their adoption in programming education remains limited due to various challenges. This study, from the instructors' perspective, explores the use of ALMs in programming education across Brazil, identifying key barriers, perceived benefits, and strategies for wider adoption through an online survey of programming instructors. The findings reveal a wide range of programming languages, tools, and platforms in use, as well as 11 key motivators and 19 benefits associated with ALM adoption. Results highlight the diversity of teaching practices, the positive impact of ALMs on student engagement and learning outcomes, and the need for institutional support and further research. By identifying the factors that influence ALM adoption, the study provides valuable insights for educators, institutions, and policymakers seeking to enhance programming instruction through more active and effective learning approaches.